PELAYANAN PUBLIK DALAM PENYELENGGARAAN PEMERINTAHAN DESA - Hartoko, Gatot; Atomy, Sri; Handayani, Putri; Laksana, April; Wahyiah, Ita Rosita (Gapenas Publisher, 2023)
Public services at the village level are the spearhead of successful governance. Good service quality will improve the welfare of the village community and strengthen community participation in development. This study aims to analyse the factors that influence the quality of public services in the village and the efforts that have been made to improve them. The research methods used are literature study and case analysis. The results show that the quality of public services in the village is influenced by several factors, such as the capacity of the village apparatus, budget availability, community participation, and local government support. Efforts to improve the quality of public services in the village include increasing the capacity of village officials through training, transparency in village budget management, and community empowerment